GPER1 signaling restricts macrophage proliferation and accumulation in human hepatocellular carcinoma - Yang, Yanyan; Wang, Yongchun; Zou, Hao; Li, Zhixiong; Chen, Weibai; Huang, Zhijie; Weng, Yulan; Yu, Xingjuan; Xu, Jing; Zheng, Limin (Frontiers in Immunology, 2024)
BackgroundSex hormones and their related receptors have been reported to impact the development and progression of tumors. However, their influence on the composition and function of the tumor microenvironment is not well understood. We aimed to investigate the influence of sex disparities on the proliferation and accumulation of macrophages, one of the major components of the tumor microenvironment, in hepatocellular carcinoma (HCC).MethodsImmunohistochemistry was applied to assess the density of immune cells in HCC tissues. The role of sex hormone related signaling in macrophage proliferation was determined by immunofluorescence and flow cytometry. The underlying regulatory mechanisms were examined with both in vitro experiments and murine HCC models.ResultsWe found higher levels of macrophage proliferation and density in tumor tissues from male patients compared to females. The expression of G protein–coupled estrogen receptor 1 (GPER1), a non-classical estrogen receptor, was significantly decreased in proliferating macrophages, and was inversely correlated with macrophage proliferation in HCC tumors. Activation of GPER1 signaling with a selective agonist G-1 suppressed macrophage proliferation by downregulating the MEK/ERK pathway. Additionally, G-1 treatment reduced PD-L1 expression on macrophages and delayed tumor growth in mice. Moreover, patients with a higher percentage of GPER1+ macrophages exhibited longer overall survival and recurrence-free survival compared to those with a lower level.ConclusionsThese findings reveal a novel role of GPER1 signaling in regulating macrophage proliferation and function in HCC tumors and may offer a potential strategy for designing therapies based on understanding sex-related disparities of patients.